Inattentional blindness and pattern-matching failure: The case of failure to recognize clinical cues. (November 2018) - Al-Moteri, Modi Owied; Symmons, Mark; Cooper, Simon; Plummer, Virginia
Abstract: Eye-tracking methodology was used to investigate lapses in the appropriate treatment of ward patients due to not noticing critical cues of deterioration. Forty nursing participants with different levels of experience participated in an interactive screen-based simulation of hypovolemic shock. The results show that 65% of the participants exhibited at least one episode of non-fixation on clinically relevant, fully visible cues that were in plain sight. Thirty-five percent of participants dwelt for sufficient time (>200 ms) on important cues for perception to take place, but no action followed, indicating they had pattern-matching failure. When participants fail to notice what, they should notice in patient status until it is too late, this can have serious consequences. Much work needs to be done, since these human perceptual limitations can affect patient safety in general wards. Highlights: Through using eye tracking approach, this study evaluates errors and lapses underlie nurses' clinical observation. In an ambiguous situation, cues obtained from clinical observation can be missed and/or misinterpreted. Perceptual limitation can affect patient safety in general wards.